Medication use and driving patterns in older drivers: preliminary findings from the LongROAD study - Linda L. Hill; Howard Andrews; Guohua Li; Carolyn G. DiGuiseppi; Marian E. Betz; David Strogatz; Patricia Pepa; David W. Eby; David Merle; Tara Kelley-Baker; Vanya Jones; Samantha Pitts (BMC, 2020)
Abstract Background The potential for impaired driving due to medication use can occur at any age, though older adults are more likely to take multiple prescribed medications and experience side effects that may affect driving ability. The purpose of this study was to characterize the relationship between medications and driving safety behaviors. Methods Data for this study came from the five-site Longitudinal Research on Aging Drivers (LongROAD) project. Participants were active drivers, age 65-79 years at enrollment, and patients at one of the 5 participating sites. Medication names and doses were obtained at baseline based on the "brown-bag review" method. Medications were coded using the American Hospital Formulary Service system. Driving data were collected by a GPS accelerometer installed in the study participants' main vehicles. Results Medication data were available for 2949 (98.6%) of the 2990 participants, and 2898 (96.9% of all participants) had both medication data and at least 30 recorded days of driving. The median number of medications taken per study participant was seven, with a range of 0-51. Total number of medications was significantly associated with a higher rapid deceleration rate. Certain medication classes were significantly associated with other driving outcomes, including central nervous system agents (more speeding events), hormones and gastrointestinal medications (more rapid decelerations), electrolytes (fewer rapid decelerations), and antihistamines (greater right to left turn ratio). Conclusions Older adult drivers are taking large quantities of prescription and non-prescription medications that may affect their driving safety. Certain medication classes are associated with potentially adverse driving patterns, such as speeding and rapid decelerations, while others are associated with potentially protective maneuvers, such as right hand turning. Further research is warranted to identify and mitigate potential adverse effects of such medications on driving safety in older adults.